STUDY OF PREGNANCY OUTCOME IN FULL TERM PREGNANT WOMEN WITH PREVIOUS ONE CAESAREAN SECTION (Indian Journal of Applied-Basic Medical Sciences, 2020)
INTRODUCTION: Caesarean section is the delivery of the foetus through the abdominal route by putting an incision on the maternal abdomen and the uterus. The goal of obstetric is a pregnancy that results in a healthy mother and infant. Most of the art of good obstetric care involves the delicate balance of avoiding caesarean delivery with its attendant complications and its application in circumstances where it is necessary for better perinatal outcome in indicated cases. Results: 72% patients underwent trial of labour after caesarean section (TOLAC) out of which 46 patients (63.8%) had successful VBAC and 26 patients (36.2%) underwent repeat emergency LSCS.Conclusion: With proper case selection, appropriate timing and close supervision of trial of labour, after prior caesarean section (TOLAC) is safe and often successful in institute having facilities for emergency caesarean section. A prior vaginal delivery is associated with higher success rate compared to no prior vaginal birth.
Keywords: VBAC (Vaginal birth after Caesarean section); TOLAC (Trial of labour after Caesarean section); ERCS (Elective repeat caesarean section); EmCS (Emergency caesarean section)